Hydrostratigraphic Assessment of Groundwater Flow System in Slopes of the Volcanic Mt. Talang, West Sumatera - Muhammad, Azwar Satrya; Endyana, Cipta; Hendarmawan, . (Journal of Geological Sciences and Applied Geology, 2017)
Mount Talang is one of the active volcanos in Indonesia, it located at Kayu Aro District, Solok Regency, West Sumatera, Indonesia, and Mount Talang is part of Barisan Mountain and lies at Sumami segment which is part of the active Sumatera Fault. In groundwater flow, a fault zone can act as a sink, or as a barrier, when the fault zone highly permeable in relation to the host rock and the fault zone must trend so as to maximize its effects, preferably parallel with general trend of the groundwater flow. Six explorations well identified at the North West Slope of Mount Talang and only two explorations well productive to be converted as exploitation well, while the others dry. Base on the geological setting, the hypothesis is faults play the role for groundwater flow. Fault occurrence analyzed from the lithology of the Bore Log each well by developed 2D hydrostratigraphic model.  Keywords: Groundwater, Hydrostratigraphy, Borehole, Volcanic.